Rate and Causes of Unplanned Hospital Returns within 60 Days following Head and Neck Surgery - Merdad, Mazin; Alqutub, Abdulsalam; Mogharbel, Ahmed; Farid, Abdullah; Bayazed, Abdullah; Alghamdi, Abdulaziz; Albogami, Yazeed; Alshehri, Rayan; Alnefaie, Majed N.; Alamoudi, Hanin A. (International Archives of Otorhinolaryngology, 2024)
Introduction Unplanned hospital returns are frequent and may be preventable.Objective To comprehend the reasons for unplanned hospital readmission and return to the Outpatient Department (OPD) and Emergency Department (ED) within 60 days after discharge following head and neck surgery (HNS) at a tertiary care center in Saudi Arabia.Methods In the present retrospective study, the medical records of all patients who underwent HNS for benign and malignant conditions between January 2015 and June 2022 were reviewed in terms of demographic data, comorbidities, and reasons for hospital return.Results Out of 1,030 cases, 119 (11.55%) returned to the hospital within 60 days after discharge, 19 of which (1.84%) were readmitted. In total, 90 (8.74%) patients returned to the OPD, and 29 (2.82%), to the ED. The common reasons for readmission included infections (26.32%) and neurological symptoms (21.05%). For OPD visits, the common causes were hematoma (20%) and neurological symptoms (14.44%). For ED returns, the frequent causes were neurological symptoms (20.69%) and equipment issues (17.24%). Compared with nonreadmitted patients, readmitted patients had a higher preoperative baseline health burden when examined using the American Society of Anesthesiologists (ASA) score (p = 0.004) and the Cumulative Illness Rating Scale (CIRS; p = 0.002).Conclusion The 60-day rates of unplanned hospital return to the OPD and ED were of 8.74% and 2.82% respectively, and 1.84% of the patients were readmitted. Hematoma, infections, and neurological symptoms were common causes. Addressing the common reasons may be beneficial to decrease postoperative hospital visits.
Keywords: patient readmission; head and neck neoplasm; surgery; otolaryngology; comorbidity